Evidence-based post-exercise recovery strategies in rugby: a narrative review - Calleja-Gonzalez, J.; Mielgo-Ayuso, J.; Ostojic, S. M.; Jones, M. T.; Marques-Jiménez, D.; Caparros, T.; Terrados, N. (The Physician and Sportsmedicine, 2019)
In the sport of rugby, athletes need a multitude of sport-specific skills along with endurance, power, and speed to optimize performance. Further, it is not unusual for athletes to play several competitive matches with insufficient recovery time. Rugby requires repeated bouts of high-intensity actions intermixed with brief periods of low-to-moderate active recovery or passive rest. Specifically, a match is characterized by repeated explosive activities, such as jumps, shuffles, and rapid changes of direction. To facilitate adequate recovery, it is necessary to understand the type of fatigue induced and, if possible, its underlying mechanisms. Common approaches to recovery may include nutritional strategies as well as active (active recovery) and passive recovery (water immersions, stretching, and massage) methods. However, limited research exists to support the effectiveness of each strategy as it related to recovery from the sport of rugby. Therefore, the main aim of the current brief review is to present the relevant literature that pertains to recovery strategies in rugby.